FACTORS AFFECTING ASSETS UTILIZATION COMPANIES ON THE INDONESIA STOCK EXCHANGE - Christian Herdinata (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Transactions that indicate tunneling can cause agency conflicts in asset usage if not resolved in the right way to address this issue. Moreover, it can have an impact on the performance of the company. This problem of agency conflict needs to be studied and find the right solution to put in place the right mechanism to control the use of assets so that in the end, it improves the performance of the company. Therefore, this research focuses on knowing the factors that influence the use of assets. The population used in this study focuses on the Indonesia Stock Exchange (IDX). The number of samples studied was 136 companies. All financial reporting data was obtained from the Indonesia Stock Exchange (IDX). Based on the results of the study, it shows that institutional ownership has a positive and significant effect on asset utilization at a significance level of 0.10. Moreover, quadratic institutional ownership has a negative and significant effect at a significance level of 0.10 on asset utilization. On the other hand, the leverage policy shows a negative and significant effect at the 0.01 level on asset utilization. Moreover, the quadratic leverage policy has a positive and significant effect at a significance level of 0.10 on asset utilization. On the other hand, asset structure has a positive and significant effect on asset utilization at the 0.05 level.